História da comunicação social: um campo em construção - Vicente, Maximiliano Martin [UNESP] (My University, 2011)
Not intending to exhaust the subject, we will attempt to show the issue status in the construction of the History of Mass Media. An initial literature review, in order to identify works relating to the subject, shows us how this issue has gone unnoticed in Academy. Expert authors in the history of every media outlet (newspaper, radio, television, movies, and more recently, internet) have been rising, but few have faced the challenge of building a History of Media. There are many reasons to justify this. It comes from the fact it is a young science, in construction, to the absence of a clear definition regarding the subject matter, sources, and methods of their own area of expertise. After all, journalism and film, for example, can be inserted in the same methodological procedure?

Sem pretender esgotar o tema, realizaremos uma tentativa de mostrar o estado da questão na construção da História da Comunicação Social. Um primeiro levantamento bibliográfico, destinado a identificar obras relacionadas ao assunto, comprova o quanto esse tema passou despercebido na academia. Proliferam os autores especializados na história de cada meio de comunicação (jornal, rádio, televisão, cinema e, ultimamente, internet), mas poucos enfrentaram o desafio de construir uma História da Comunicação Social. Razões para justificar essa lacuna não faltam. Vão desde o fato de se tratar de uma ciência jovem, portanto em construção, até a ausência de uma definição clara em relação ao objeto, fontes e métodos próprios dessa área de conhecimento. Afinal, o jornalismo e o cinema, por exemplo, podem ser inseridos num mesmo procedimento metodológico?
History of the Media: a field under construction
Keywords: History; Media; Communication science; História; Comunicação social; Ciência da comunicação